2008
DOI: 10.1007/s11999-008-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Management in Rotationplasty

Abstract: The Van Nes rotationplasty is a useful limbpreserving procedure for skeletally immature patients with distal femoral or proximal tibial malignancy. The vascular supply to the lower limb either must be maintained and rotated or transected and reanastomosed. We asked whether there would be any difference in the ankle brachial index or complication rate for the two methods of vascular management. Vessels were resected with the tumor in seven patients and preserved and rotated in nine patients. One amputation occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The most devastating complication after rotationplasty is vascular compromise of the rotated limb, which can result in eventual above-the-knee amputation or hip disarticulation. Although reported rates of vascular compromise after conventional rotationplasty range from 3.7% to 15.4% [ 1 , 2 , 12 ], the rate only after rotationplasty for revision of infected prosthesis has never been reported. In the conventional method of Van Nes rotationplasty, the femoropopliteal artery and vein are preserved with the sciatic nerve, the neurovascular structures are coiled, and the distal limb is rotated axially 180° and reattached to the proximal stump.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most devastating complication after rotationplasty is vascular compromise of the rotated limb, which can result in eventual above-the-knee amputation or hip disarticulation. Although reported rates of vascular compromise after conventional rotationplasty range from 3.7% to 15.4% [ 1 , 2 , 12 ], the rate only after rotationplasty for revision of infected prosthesis has never been reported. In the conventional method of Van Nes rotationplasty, the femoropopliteal artery and vein are preserved with the sciatic nerve, the neurovascular structures are coiled, and the distal limb is rotated axially 180° and reattached to the proximal stump.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the optimal method of vascular management of rotationplasty after the resection of primary sarcomas, no consensus has been reached [ 12 , 13 ]. However, vascular transection and reanastomosis would be the preferred vascular management method for rotationplasty performed for revision of infected prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this patient, rotationplasty type A was performed while preserving major neurovascular bundles. However, if the margin of control became vulnerable with contamination of the vessels, a vascular bypass surgery may be necessary, and vascular anastomosis did not increase the risk of rotationplasty failure [13]. Many incision and surgical techniques had been reported to facilitate the ease of the operation while minimizing the complications [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether one method results in superior outcomes and a lower complication rate. Mahoney et al 44 examined the ankle brachial indices and complication rates in two groups of patients managed with each technique and concluded that both vascular management options are safe and that the complication rates are equal.…”
Section: Limb-salvage Surgerymentioning
confidence: 99%